Implementation of the Mandatory Policy on the Use of Environmentally Friendly Shopping Bags in Jakarta - Rifani, Hilda; Ilham, Muh.; Amalia, Rizki (International Journal Labs, 2025)
The volume of waste from the people of Jakarta reaches 7,500 tons every day, 14% or 1,000 tons is single-use plastic waste. It is estimated that every day there are 650-800 thousand plastic bags that enter the Bantargebang TPST. The thing to worry about from the massive use of plastic shopping bags, plastic shopping bags made from plastic (polyolefin or polyvinyl chloride) can be a threat to Humans and the Earth, in this case plastic shopping bags take 10 to 20 years to be destroyed, even taking up to hundreds to be able to decompose completely. This study uses a qualitative method with a descriptive approach using policy implementation theory from Grindle (1980) with primary and secondary data sources. Data collection techniques are carried out by interviews, observations and documentation, data analysis techniques used are data reduction, data presentation and conclusion drawn. The results of this study show that the implementation of the mandatory policy on the use of environmentally friendly shopping bags in DKI Jakarta has been implemented well, but there are still inhibiting factors in the use of environmentally friendly shopping bags. The factors inhibiting the implementation of the mandatory policy on the use of environmentally friendly shopping bags in DKI Jakarta are: limited socialization and communication, resistance from business actors, supervision that is not optimal, and lack of interest of business actors in providing environmentally friendly shopping bags. Efforts are made to overcome obstacles to the implementation of the mandatory policy on the use of environmentally friendly shopping bags in DKI Jakarta, namely: socialization and public education, support and incentives for traders and business actors, strengthening regulations and supervision, and affordable shopping bag alternatives.